Enhancing Students’ Ability in Writing Descriptive Text through Graphic Organizers - Maslichah Maslichah; Siti Tarwiyah (Vision: Journal for Language and Foreign Language Learning, 2017)
Graphic organizers are visual displays of crucial content information designed to benefit learners who have difficulty organizing information and it could help the students to build and generate ideas. The study was aimed at finding the answers to the following research questions: (1) How is the implementation of graphic organizers to enhance students' ability in writing the descriptive text? (2) How is the enhancement of students' ability in writing descriptive text through graphic organizers? This study was a classroom action research. The data were obtained through documentation, observation, and test. It was conducted in three cycles with the 24 eighth grade students of MTs Nurul Islam Juwangi in the academic year of 2016/2017. The result of this research showed that students’ ability was improved in each cycle after they were taught using graphic organizers. They were better in their descriptive text writing concerning content, organization, vocabulary, language use, and mechanic.